2008
DOI: 10.1093/jee/101.4.1276
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Host Associations of Redbay Ambrosia Beetle (Coleoptera: Curculionidae: Scolytinae), Exotic Vector of Laurel Wilt Killing Redbay Trees in the Southeastern United States

Abstract: The redbay ambrosia beetle, Xyleborus glabratus Eichhoff (Coleoptera: Curculionidae: Scolytinae), and its fungal symbiont, Raffaelea sp., are new introductions to the southeastern United States responsible for the wilt of mature redbay, Persea borbonia (L.) Spreng., trees. In 2006 and 2007, we investigated the seasonal flight activity of X. glabratus, its host associations, and population levels at eight locations in South Carolina and Georgia where infestations ranged from very recent to at least several year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 0 publications
0
52
0
1
Order By: Relevance
“…After departing the natal tree, females (usually sibling mated) orient toward long-range olfactory cues while in flight. It does not appear that X. glabratus utilizes sex or aggregation pheromones, since bolts from trees infested with conspecifics are no more attractive than bolts from uninfested trees [2]. As primary colonizers of healthy trees [1], females are attracted to natural volatiles emitted by host Lauraceae [29], [31], and the current study identified four sesquiterpenes that were correlated with attraction: α-cubebene, α-copaene, α-humulene, and calamenene.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…After departing the natal tree, females (usually sibling mated) orient toward long-range olfactory cues while in flight. It does not appear that X. glabratus utilizes sex or aggregation pheromones, since bolts from trees infested with conspecifics are no more attractive than bolts from uninfested trees [2]. As primary colonizers of healthy trees [1], females are attracted to natural volatiles emitted by host Lauraceae [29], [31], and the current study identified four sesquiterpenes that were correlated with attraction: α-cubebene, α-copaene, α-humulene, and calamenene.…”
Section: Discussionmentioning
confidence: 64%
“…and P. palustris (Raf.) Sarg., respectively] have been decimated throughout the southeastern United States [1][2], and currently avocado ( P. americana Mill.) is threatened in south Florida [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One vector of Lw disease is the redbay ambrosia beetle [3,4,7,8]. The redbay ambrosia beetle, Xyleborus glabratus Eichhoff (Coleoptera, Curculionidae, Scolytinae) is associated with fungal symbionts such as Raffaelea lauricola [9,10], a fungus that kills the tree by blocking water flow to the canopy [11].…”
Section: Introductionmentioning
confidence: 99%